Spectroscopic characterisation of wood treated by different coatings after weathering in subarctic conditions - Myronycheva, Olena; Sekan, Alona; Kim, Injeong; Karlsson, Olov; Jacobsson, Peter; Sehlstedt-Persson, Margot; Sandberg, Dick (Luleå tekniska universitet, Träteknik, 2020)
Weathering of wood is a complex natural phenomenon that is influenced by factors both in macro and micro-scale. The degradation by weathering constitutes of complex physical-chemical changes influenced by environmental factors such as moisture, sunlight, temperature, chemical compounds, wind, and biological organisms and their related agents. The aim of our study was the evaluation of MIR and NIR spectroscopic technique for characterisation of wood treated by commercial coatings contained different biocidal treatments after weathering in subarctic conditions. Tangential and radial surfaces of the Scots pine and Norway spruce were treated with coatings containing various biocides. Treatment was in the form of fairly transparent wood oil (T), while the two others were coatings that had more of a non-transparent character (H and P). Treatedspecimens and control were placed in various directions on racks outdoor for natural weathering. The measurement of the NIR spectra of specimens that were not exposed, after weathering and dried after weathering, was done by the point-based microNIR portable sensor. Multivariate statistical analysis (MSA) showed that data from types of exposure contributed to less compared to surface treatments in the 3D principal component analysis model (PCA). Grouping pattern around treatments H and P could be obtained as the two individual groups more or less fully separated. From the treatment T and non-treated specimens, no individual grouping behaviour could be observed, however, more intense exposed seemed to be clustered in a different way than mildly exposed ones. A more extensive weather exposure gave also a more degraded surface for T-treated specimens. The NIR portable spectrometer may be used for assessment of the extent of weathering, but the treatment P followed by treatment H had minimal changes. Coefficients Plot in the PLSDA model for different types of exposure for those treatments showed the influence of the NIRwavelengths in classes related to exposure type. The changes ...